Application of didactic resources in the teaching learning process of the English language for students of first and second year of bachillerato of Colegio Fiscal Tecnico Dr. Juan Henríquez Coello, in Machala city, academic year 2014-2015. - Mizhquiri Manzano, Eliana Belén (2014)
The phenomenon of globalization has contributed greatly to make English the most important and necessary language currently being treated as the language of developed countries, given high rates of growth around the world.